Pembelajaran Seni Tari dan Seni Musik terhadap Kreativitas Kemampuan Motorik Anak Usia Dini - Irda Wahyuni Hasibuan; Nabila Dwirizki Handayani; Putri Amelia; Rahmania Hasibuan (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
In the development of children's motor skills is also influenced by the environment, another thing is the difficulty of children in following learning, some are still accompanied and assisted by their parents, some are not confident, do not want to gather with friends, have difficulty adjusting to their environment. This study aims to determine the interaction between dance learning and music creativity learning on gross motor skills. This study uses a literature review approach, this method is an activity that examines various references and results of previous similar studies, which are useful for obtaining a theoretical basis for the problems studied by reading various books or sources. The results of the study showed an interaction between dance learning and music learning on children's gross motor skills creativity.